The Appointment and Dismissal Procedure of the Polish NCA in the Light of EU and International Independence Standards - Małobęcka-Szwast, Iga (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
Since Regulation 1/2003 entered into force, NCAs have been vested with application of the EU competition rules concurrently with the European Commission. Although it is acknowledged that a sufficient degree of NCAs’ independence is indispensable for effective enforcement of the EU competition law, the EU law has so far not provided any specific requirements with regard to the independence of the NCAs, in particular the appointment and dismissal procedure of the NCA’s management and its term of office. Against this background, the conditions of the appointment and dismissal of the President of the OCCP were analysed and it was inferred that in the current form they may infringe upon the authority’s independence, as well as undermine its credibility and legitimacy. In order to find an optimal design of appointment and dismissal procedures, the NCAs from two other Member States were investigated. Finally, a set of recommendations for both the national and European legislator was proposed, which could improve the independence and effectiveness of the Polish NCA. These include introducing a non-renewable fixed term of at least 5 years, specifying grounds for dismissal and obliging the Prime Minister to make them public, engaging the Parliament in the appointment procedure and public hearings of the candidates.
Keywords: President of the Office for Competition and Consumer Protection; EU law; independence; competition law; national competition authority